Efficient strengthening technique to increase the flexural resistance of existing RC slabs - Bonaldo, Everaldo (2008)
Composite materials are being used with notable effectiveness to increase and upgrade the flexural load carrying capacity of reinforced concrete (RC) members. Near-Surface Mounted (NSM) is one of the most promising strengthening techniques, based on the use of carbon fiber-reinforced polymer (CFRP) laminates. According to NSM, the laminates are fixed with epoxy based adhesive into slits opened into the concrete cover on the tension face of the elements to strength. Laboratory tests have shown that the NSM technique is an adequate strengthening strategy to increase the flexural resistance of RC slabs. However, in RC slabs of low concrete strength, the increase of the flexural resistance that NSM can provide is limited by the maximum allowable compressive strain in the compressed part of the slab, in order to avoid concrete crushing. This restriction reduces the effectiveness of the strengthening, thus limiting the use of the NSM technique. A new thin layer of concrete bonded to the existing concrete at the compressed region is suitable to overcome this limitation. Volumetric contraction due to shrinkage and thermal effects can induce uncontrolled cracking in the concrete of this thin layer. Adding steel fibers to concrete (Steel Fiber Reinforced Concrete - SFRC), the post cracking residual stress can be increased in order to prevent the formation of uncontrolled crack patterns. In the present work, the combined strengthening strategy, a SFRC overlay and NSM CFRP laminates, was applied to significantly increase the flexural resistance of existing RC slabs. Experimental results of four-point bending tests, carried out in unstrengthened and strengthened concrete slab strips, are presented and analyzed.